Graphite negative electrode active material and preparation method thereof, secondary battery and electric device

By controlling the graphitization degree and oil absorption value of graphite negative electrode active material, the problems of short cycle life and poor storage performance of secondary batteries are solved, and the long cycle life and high energy density of the battery are achieved.

CN119852400AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311676609.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

Existing secondary batteries have problems with short cycle life and poor storage performance during long cycle use. Especially in large energy storage power plants, energy storage batteries with longer cycle life need to be developed.

Method used

A graphite negative electrode active material is provided, with a graphitization degree of 88%-93%, and an oil absorption value does not exceed 50ml/100g. By controlling these parameters, the cycle performance and storage performance of the battery are improved.

Benefits of technology

By improving the dispersion and uniformity of graphite negative electrode active materials, reducing the polarization and lithium-ion phenomena of electrode sheets, significantly extending the service life and storage life of the battery, and improving the energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852400A_ABST
    Figure CN119852400A_ABST
Patent Text Reader

Abstract

The invention provides a graphite negative electrode active material and a preparation method thereof, a secondary battery and an electric device, the graphitization degree of the graphite negative electrode active material is 88-93%, and the oil absorption value of the graphite negative electrode active material is not more than 50ml / 100g. The graphite negative electrode active material can improve the cycle performance of the battery and prolong the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a graphite negative electrode active material and a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] With the introduction of carbon neutrality goals and policies, the secondary battery market for energy storage has ushered in a huge explosion. For energy storage batteries, long cycle life is a key indicator, especially for energy storage batteries used in large-scale energy storage power stations. In order to extend service life and reduce replacement frequency, it is necessary to further develop energy storage batteries with longer cycle life. Summary of the invention

[0003] This application is made in view of the above-mentioned problems, and its purpose is to provide a graphite negative electrode active material and a preparation method thereof, a secondary battery and an electrical device, which can effectively improve the cycle life of the battery and extend the service life of the battery. …

[0004] A first aspect of the present application provides a graphite negative electrode active material, wherein the graphitization degree of the graphite negative electrode active material is 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50 ml / 100 g.

[0005] On the one hand, the oil absorption value of the graphite negative electrode active material is controlled not to exceed 50ml / 100g, the graphite negative electrode active material has good dispersibility in the negative electrode slurry, the negative electrode slurry has excellent anti-sedimentation property, it is easy to control the coating weight during the electrode coating process, it is easy to prepare the electrode sheet with uniform distribution and uniform thickness of the graphite negative electrode active material, reduce the possibility of uneven local current density during charging and discharging, reduce the lithium precipitation phenomenon caused by the polarization of the electrode sheet, improve the cycle performance and storage performance of the battery, and extend the service life of the battery. On the other hand, the graphitization degree of the graphite negative electrode active material is controlled to be 88%-93%, the interlayer spacing of the graphite negative electrode active material is large, which is conducive to the rapid deintercalation of active ions, and the expansion of the graphite negative electrode active material is small when the active ions are embedded in the negative electrode, which is conducive to the long cycle of the battery. At the same time, the appropriate graphitization degree is conducive to improving the gram capacity of the graphite negative electrode active material, providing a material basis for the preparation of high energy density batteries.

[0006] In summary, graphite negative electrode active materials that meet the above requirements are beneficial to improving the cycle performance and storage performance of the battery, and the battery has a high energy density.

[0007] In any embodiment, the oil absorption value of the graphite negative electrode active material is 30 ml / 100 g-43 ml / 100 g.

[0008] As mentioned above, the smaller the oil absorption value of the graphite negative electrode active material, the better its dispersibility in the negative electrode slurry, which is conducive to the preparation of a negative electrode sheet with uniform graphite distribution, and can improve the cycle performance of the battery. However, if the oil absorption value of the graphite negative electrode active material is too small, there are high requirements for the particle regularity or particle size distribution of the graphite negative electrode active material, and the cost of the graphite negative electrode active material is high, which is not conducive to industrial promotion.

[0009] By controlling the oil absorption value of the graphite negative electrode active material within a suitable range and meeting the requirements of long cycle performance, the cost of the graphite negative electrode active material can be reduced, which is conducive to industrial production.

[0010] In any embodiment, the particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.2-1.6.

[0011] The particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is within the above range. On the one hand, the oil absorption value of the graphite can be regulated to a lower value, which is beneficial to improve the uniformity of the negative electrode slurry and the uniformity of the graphite negative electrode active material in the negative electrode sheet. At the same time, it can also reduce the negative impact of large-particle graphite negative electrode active materials on the cycle performance and storage performance, thereby comprehensively improving the cycle performance and storage performance of the battery.

[0012] In any embodiment, based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material accounts for greater than or equal to 85%, and can be optionally 85%-100%.

[0013] Compared with secondary particles, primary particles have fewer gaps between particles, and the surface angles of primary particles are smaller, the particle morphology is smoother, the oil absorption value of graphite negative electrode active materials is smaller, and the leveling performance of the slurry is better, which is conducive to the preparation of negative electrode sheets with uniform distribution of graphite negative electrode active materials and improves the cycle performance of the battery. At the same time, compared with secondary particles, primary particles have better structural stability and are not easy to break during the cycle process, which improves the cycle performance of the battery.

[0014] In any embodiment, the specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g, optional 0.6m 2 / g-1.3m 2 / g.

[0015] The graphite negative electrode active material has a low specific surface area, which is conducive to obtaining a graphite negative electrode active material with a low oil absorption value. At the same time, it also makes the graphite negative electrode active material have a low surface activity, thereby reducing the consumption of active ions by SEI film formation and improving the cycle performance and storage performance of the battery.

[0016] In any embodiment, the volume distribution particle size Dv50 of the graphite negative electrode active material is 12 μm-16 μm, and can be optionally 13 μm-15 μm.

[0017] The graphite negative electrode active material has a large volume distribution particle size Dv50, and the negative electrode film layer has a large pore size, which is conducive to the electrolyte fully infiltrating the negative electrode plate, reducing the possibility of local polarization of the plate, and reducing the impact of black spots on the negative electrode on the cycle life and storage performance of the battery.

[0018] In any embodiment, the graphite negative electrode active material satisfies at least one of the following:

[0019] (1) The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.70g / cm 3 -1.85g / cm 3 ;

[0020] (2) The tap density of the graphite negative electrode active material is 1.2 g / cm 3 -1.4g / cm 3 ;

[0021] (3) The gram capacity of the graphite negative electrode active material is greater than or equal to 340 mAh / g, and can be optionally 341 mAh / g-347 mAh / g.

[0022] The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is within a suitable range, which can further improve the cycle performance of the battery.

[0023] When the tap density of the graphite negative electrode active material is within the above range, the compaction density of the negative electrode plate can be increased, thereby increasing the energy density of the secondary battery; it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improving the transmission performance of active ions and electrons, and improving the cycle performance and storage performance of the secondary battery.

[0024] Graphite negative electrode active materials have high gram capacity, providing a material basis for high energy density batteries. At the same time, the gram capacity of graphite negative electrode active materials is within the above range, the lattice expansion of the material during the cycle is relatively small, the crystal structure stability is good, the irreversible consumption of active ions is reduced, and the cycle performance and storage performance of the battery are improved.

[0025] The present application also provides a method for preparing a graphite negative electrode active material, which is characterized by comprising the following steps:

[0026] Provide raw materials;

[0027] Processing the raw material to obtain a precursor;

[0028] The precursor is graphitized to obtain an intermediate product;

[0029] The intermediate product is subjected to screening treatment to obtain a graphite negative electrode active material; the graphitization degree of the graphite negative electrode active material is 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50ml / 100g.

[0030] By adopting the above preparation method, a graphite negative electrode active material with low oil absorption value and low graphitization degree can be prepared, which can improve the cycle performance of the battery and extend the service life of the battery.

[0031] In any embodiment, the raw material includes at least one of petroleum coke, needle coke, and pitch coke, and petroleum coke can be selected.

[0032] Based on the total volume of the raw material structure, the volume proportion of the mosaic type and regional type structure is greater than or equal to 50%, and can be optionally 50%-65%.

[0033] In any embodiment, the bonding index of the raw material is less than or equal to 10, and can be optionally 1-9.

[0034] In any embodiment, the precursor satisfies at least one of the following conditions:

[0035] The volume distribution particle size Dv50 of the precursor is 12 μm-18 μm; and / or,

[0036] The particle size distribution of the precursor (Dv90-Dv10) / Dv50 is 1.2-1.8.

[0037] Controlling the volume distribution particle size Dv50 or particle size distribution (Dv90-Dv10) / Dv50 of the precursor within a suitable range is conducive to controlling the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material within a suitable range, thereby regulating the oil absorption value of the graphite negative electrode active material within a smaller range.

[0038] In any embodiment, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization equipment.

[0039] In any embodiment, the maximum power of the graphitization treatment is 23000W-25000W; and / or the constant power time of the graphitization treatment at the maximum power is 10h-50h.

[0040] In any embodiment, the screening process of the intermediate product specifically comprises the following steps:

[0041] The intermediate product is sieved to remove particles with a maximum particle size Dmax greater than 100 μm, thereby obtaining a graphite negative electrode active material.

[0042] Remove large-size particles from intermediate products to reduce the negative impact of large particle materials on battery cycle performance and storage performance.

[0043] The third aspect of the present application provides a secondary battery, including a negative electrode plate, wherein the negative electrode plate includes a negative electrode collector and a negative electrode film layer formed on at least one surface of the negative electrode collector, and the negative electrode film layer includes the graphite negative electrode active material of the first aspect of the present application or the graphite negative electrode active material prepared by the preparation method of the second aspect.

[0044] In any embodiment, the negative electrode film layer includes a conductive agent, and based on the mass of the negative electrode film layer, the mass content of the conductive agent is greater than or equal to 1.5%, and can be optionally 1.8%-2.5%.

[0045] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0047] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0048] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0049] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0050] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0051] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0052] Description of reference numerals:

[0053] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0054] Hereinafter, the embodiments of the graphite negative electrode active material and its preparation method, secondary battery and electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0058] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0060] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] The negative electrode active material is the main material of the battery. The purpose of storing electricity is achieved by storing lithium in the negative electrode active material during charging. The performance of the negative electrode active material has an important influence on the cycle life of the battery. In the prior art, in order to obtain a long cycle battery, the graphitization degree of the negative electrode active material or the compaction density of the negative electrode plate and other parameters are generally controlled to obtain a battery with a long cycle life. However, another factor that affects the capacity decay is the uniformity of the active material in the negative electrode plate. If the negative electrode active material is unevenly mixed with the conductive agent, binder, etc. during the preparation of the negative electrode slurry, the negative electrode slurry will settle or agglomerate, and the active material distribution in the negative electrode plate formed by coating will be uneven or the thickness of the plate will be uneven, which can easily cause local current unevenness during the cycle. The difference in the diffusion concentration of active ions causes lithium precipitation and capacity decay, affecting the cycle performance and storage performance of the battery.

[0062] [Graphite negative electrode active material]

[0063] Based on this, the present application proposes a graphite negative electrode active material, wherein the graphitization degree of the graphite negative electrode active material is 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50ml / 100g.

[0064] In some embodiments, the graphitization degree of the graphite negative electrode active material may be any value selected from 88%, 89%, 90%, 91%, 92%, 93%, or a range consisting of any two values ​​thereof.

[0065] In this article, the term "degree of graphitization" macroscopically characterizes the proportion of the material that reaches a complete graphite crystal structure; microscopically, it refers to the degree to which the carbon structure in different transition states is close to the ideal graphite crystal.

[0066] The graphitization degree of graphite negative electrode active materials reflects the completeness of the graphite crystal structure in the material, that is, the regularity of the arrangement of carbon atoms in the graphite structure in the material. A material with a high graphitization degree indicates that the distance between graphite layers is small, the smaller the lattice rotation, the less scattered stacking of the layers, the more orderly the arrangement, and the high gram capacity of the material, which is conducive to obtaining a secondary battery with high energy density. A material with a low graphitization degree indicates that the distance between graphite layers is large, which is conducive to the rapid deintercalation of active ions, the expansion of the material is small when lithium is inserted, and it has the effect of shallow charge and discharge, which is conducive to long cycles and long storage.

[0067] In the present application, the graphitization degree of the graphite negative electrode active material is a well-known meaning in the art, and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing, and the test can refer to JISK 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d002 of the C(002) crystal plane in the material crystal structure, and then the graphitization degree is calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal plane in the material crystal structure expressed in nanometers (nm).

[0068] In some embodiments, the oil absorption value of the graphite negative electrode active material may be any one of no more than 30 ml / 100 g, no more than 35 ml / 100 g, no more than 40 ml / 100 g, no more than 45 ml / 100 g, and no more than 50 ml / 100 g.

[0069] In this article, the term "oil absorption value" refers to the volume of linseed oil that can be absorbed by 100g of graphite negative electrode active material. For example, if the oil absorption value of the graphite negative electrode active material is 40ml / 100g, it means that 100g of the graphite negative electrode active material can absorb 40ml of linseed oil.

[0070] The oil absorption value of the graphite negative electrode active material can be tested by methods and equipment known in the art, as shown below: obtain the test oil and the graphite negative electrode active material sample respectively, and set the torque threshold of the oil absorption value tester; add the oil to the sample in the mixing chamber of the oil absorption value tester at a constant speed, and as the oil absorption of the sample increases, the viscosity of the mixture of the sample and the oil continues to increase. When the viscosity of the mixture reaches the preset torque threshold of the oil absorption value tester, stop and calculate the volume of the sample absorbed by unit mass, which is the oil absorption value QI of the sample. The test oil is linseed oil (DBP), and the torque threshold is 1N.

[0071] The oil absorption value of graphite negative electrode active materials is mainly related to the specific surface area of ​​the material, the surface properties of the material, the particle shape of the material and the particle size distribution of the material. The oil absorption value of graphite negative electrode active materials reflects the dispersibility of the material in the negative electrode slurry. The material has a small oil absorption value, and has excellent dispersibility in the negative electrode slurry. The negative electrode slurry has excellent anti-sedimentation and dispersibility. It is easy to control the coating weight during the coating process of the electrode sheet, and prepare the negative electrode sheet with uniform distribution and uniform thickness of graphite negative electrode active materials, reduce the possibility of local current density unevenness during charging and discharging, reduce the lithium precipitation phenomenon caused by the polarization of the electrode sheet, improve the cycle performance of the battery, and extend the service life and storage life of the battery.

[0072] In summary, the graphite negative electrode active material has a suitable range of graphitization degree and oil absorption value, which is beneficial to improving the cycle performance and storage performance of the battery, and the battery has a high energy density.

[0073] In some embodiments, the oil absorption value of the graphite negative electrode active material is 30ml / 100g-43ml / 100g. In some embodiments, the oil absorption value of the graphite negative electrode active material can be selected from any value of 30ml / 100g, 32ml / 100g, 34ml / 100g, 36ml / 100g, 38ml / 100g, 40ml / 100g, 42ml / 100g, 43ml / 100g, or a range consisting of any two of them.

[0074] As mentioned above, the smaller the oil absorption value of the graphite negative electrode active material, the better its dispersibility in the negative electrode slurry, which is conducive to the preparation of a negative electrode sheet with uniform graphite distribution, and can improve the cycle performance of the battery. However, if the oil absorption value of the graphite negative electrode active material is too small, there are high requirements for the particle regularity or particle size distribution of the graphite negative electrode active material, and the cost of the graphite negative electrode active material is high, which is not conducive to industrial promotion.

[0075] By controlling the oil absorption value of the graphite negative electrode active material within a suitable range and meeting the requirements of long cycle performance, the cost of the graphite negative electrode active material can be reduced, which is conducive to industrial production.

[0076] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is 1.2-1.6. In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material can be selected as any value among 1.2, 1.3, 1.4, 1.5, 1.6 or a range consisting of any two values ​​therein.

[0077] The volume distribution particle sizes Dv10, Dv50, and Dv90 of the graphite negative electrode active material are well known in the art, and respectively represent the particle sizes corresponding to the cumulative volume distribution percentages of the material reaching 10%, 50%, and 90%, and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer with reference to the particle size distribution laser diffraction method of GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0078] The particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material will affect the oil absorption value of the material. When the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is too large, the oil absorption value of the graphite negative electrode active material is large, and the small and large particle sizes of the graphite negative electrode active material hinder the dispersion of the graphite negative electrode active material in the negative electrode slurry, which will have an adverse effect on the uniformity and thickness of the pole piece, and deteriorate the cycle performance of the battery. When the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is too small, the preparation process of the graphite negative electrode active material is relatively complicated, the yield of the graphite negative electrode active material decreases significantly, and the cost increases significantly.

[0079] In summary, the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material is within an appropriate range, the oil absorption value of the graphite negative electrode active material is low, the battery cycle performance is excellent, and at the same time it can reduce the cost of the graphite negative electrode active material, which is conducive to industrial application.

[0080] In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material accounts for greater than or equal to 85%.

[0081] In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material accounts for 85%-100%. In some embodiments, based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material can be any value among 85%, 90%, 95%, 100%, or a range consisting of any two values ​​therein.

[0082] In some embodiments, the particles in the graphite negative electrode active material include primary particles and secondary particles. Herein, primary particles and secondary particles are both well known in the art. "Secondary particles" refer to agglomerated particles formed after agglomeration between multiple primary particles or primary particles. The force for agglomeration between particles can be assisted by another substance (e.g., a sticky chemical substance) to assist agglomeration.

[0083] The number ratio of primary particles can be determined by instruments and methods known in the art. An example is as follows: lay and stick the graphite negative electrode active material on the conductive glue to make a sample to be tested with a length × width = 6 cm × 1.1 cm. Use a scanning electron microscope; an energy spectrometer (such as ZEISS SEM (sigma300)) to test the morphology of the particles in the sample to be tested. The test can refer to JY / T010-1996. In order to ensure the accuracy of the test results, multiple (for example, 10 or 20) different areas can be randomly selected from the sample to be tested for scanning testing, and at a certain magnification (for example, 500 times or 1000 times), the number of secondary particles and the total number of particles in the test area are counted. The ratio of the number of primary particles to the total number of particles in any test area is the number ratio of primary particles in the area, and the average value of the test results of 10 test areas is taken as the number ratio of primary particles. In order to ensure the accuracy of the results, multiple samples to be tested (for example, 5 or 10) may be prepared to repeat the above test, and the average value of the test results of each sample to be tested is taken as the percentage of primary particles in the graphite negative electrode active material.

[0084] Compared with secondary particles, primary particles have fewer gaps between particles, and the surface angles of primary particles are smaller, the particle morphology is smoother, the oil absorption value of graphite negative electrode active materials is smaller, and the leveling performance of the slurry is better, which is conducive to the preparation of negative electrode sheets with uniform distribution of graphite negative electrode active materials and improves the cycle performance of the battery. At the same time, compared with secondary particles, primary particles have better structural stability and are not easy to break during the cycle process, which improves the cycle performance of the battery.

[0085] In some embodiments, the specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g.

[0086] In some embodiments, the specific surface area of ​​the graphite negative electrode active material can be 0.4 m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.85m 2 / g, 0.85m 2 / g, 1.05m 2 / g, 1.15m 2 / g, 1.25m 2 / g, 1.3m 2 / g, 1.4m 2 Any value in / g or a range consisting of any two values ​​in it.

[0087] As used herein, the term "specific surface area" refers to the sum of the total external surface areas of all particles per gram of material.

[0088] The specific surface area of ​​the graphite negative electrode active material can be measured by instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017, and calculated by BET (BrunauerEmmett Teller) method, wherein the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0089] The specific surface area of ​​the graphite negative electrode active material will affect the oil absorption value of the material. A low specific surface area will result in a low oil absorption value, thereby improving the distribution uniformity of the graphite negative electrode active material in the negative electrode sheet and the uniformity of the electrode sheet thickness, and improving the battery's cycle performance and storage performance. At the same time, the graphite negative electrode active material has a low specific surface area, which makes the material have low surface activity, thereby reducing the consumption of active ions by SEI film formation and improving the battery's cycle performance and storage performance.

[0090] In some embodiments, the specific surface area of ​​the graphite negative electrode active material is 0.6 m 2 / g-1.3m 2 / g.

[0091] In some embodiments, the specific surface area of ​​the graphite negative electrode active material can be 0.6 m 2 / g, 0.7m 2 / g, 0.75m 2 / g, 0.85m 2 / g, 0.85m 2 / g, 1.05m 2 / g, 1.15m 2 / g, 1.25m 2 / g, 1.3m 2 Any value in / g or a range consisting of any two values ​​in it.

[0092] As mentioned above, graphite negative electrode active materials have a small specific surface area and low oil absorption value, which is beneficial to the cycle life of the battery. However, if the specific surface area is too small, it will affect the wettability of the electrolyte to the electrode, affect the kinetic performance of the electrode, and easily cause lithium precipitation, which will affect the cycle life and storage life of the battery. The appropriate range of specific surface area can further improve the cycle life and storage life of the battery.

[0093] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 12 μm-16 μm.

[0094] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material can be selected as any value of 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm, 15.5μm, 16μm, or a range consisting of any two values ​​thereof.

[0095] The graphite negative electrode active material has a large volume distribution particle size Dv50, and the negative electrode film layer has a large pore size, which is conducive to the electrolyte fully infiltrating the negative electrode plate, reducing the possibility of local polarization of the plate, and reducing the impact of black spots on the negative electrode on the cycle life and storage performance of the battery.

[0096] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material is 13 μm-15 μm.

[0097] In some embodiments, the volume distribution particle size Dv50 of the graphite negative electrode active material can be selected as any value of 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, or a range consisting of any two values ​​thereof.

[0098] The graphite negative electrode active material has a suitable volume distribution particle size Dv50, and the negative electrode film layer has a suitable pore size, which is conducive to the electrolyte fully infiltrating the negative electrode plate, reducing the possibility of local polarization of the plate, and reducing the impact of black spots on the battery cycle life and storage performance. At the same time, it is conducive to improving the transmission performance of active ions and electrons. The plate has excellent kinetic performance and reduces the impact of lithium precipitation on the battery life.

[0099] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is less than or equal to 1.85g / cm 3 .

[0100] In this article, the term "powder compaction density" refers to the density of the powder to be tested under a preset pressure.

[0101] The method for measuring the compacted density of the powder can be any method known in the art. For example, referring to GB / T24533-2009, 1g of graphite negative electrode active material powder is weighed and added to a bottom area of ​​1.327cm 2 The mold is pressurized to a specific pressure, such as 49000N, and the pressure is maintained for 30 seconds, then the pressure is released and maintained for 10 seconds. The powder compaction density of the graphite negative electrode active material under the selected pressure is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0102] When the graphite powder compaction density of the graphite negative electrode active material under a pressure of 49000N is greater than 1.85g / cm 3 The particle strength of the graphite negative electrode active material is not enough. It is constantly squeezed during the cycle and it is difficult to maintain the original pore structure of the electrode. It will change the tortuosity of the electrode, increase the lithium ion insertion path, affect the battery's kinetic performance, and is not conducive to achieving long-term cycle stability.

[0103] In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is 1.70g / cm 3 -1.85g / cm 3 In some embodiments, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N may be 1.70 g / cm 3 , 1.72g / cm 3 , 1.74g / cm 3 , 1.76g / cm 3 , 1.78g / cm 3 , 1.80g / cm 3 , 182g / cm 3 、1.84g / cm 3 , 1.85g / cm 3 Any value in , or a range of any two values ​​in .

[0104] As mentioned above, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N is less than or equal to 1.85g / cm 3 , which is beneficial to improving the cycle performance of the battery. At the same time, the powder compaction density of the graphite negative electrode active material under a pressure of 49000N will also affect the energy density of the battery. The higher the powder compaction density, the greater the compaction density of the negative electrode film layer, which is more conducive to increasing the energy density of the secondary battery.

[0105] By controlling the powder compaction density of the graphite negative electrode active material under a pressure of 49000N within an appropriate range, the cycle life of the battery can be improved while also taking into account the high energy density of the battery.

[0106] In some embodiments, the tap density of the graphite negative electrode active material is 1.2 g / cm 3 -1.4g / cm 3 In some embodiments, the tap density of the graphite negative electrode active material may be 1.2 g / cm 3 , 1.25g / cm 3 , 1.30g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 Any value in , or a range of any two values ​​in .

[0107] In this article, the term "tap density" refers to the density of a powder material after vibration compression under certain conditions.

[0108] The tap density can be measured by any method known in the art. For example, GB / T5162-2006 can be referred to and the tap density of a powder can be measured by a powder tap density tester. The test instrument can be Dandong Better BT-301.

[0109] When the tap density of the graphite negative electrode active material is within the above range, the compaction density of the negative electrode plate can be increased, thereby increasing the energy density of the secondary battery; it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improving the transmission performance of active ions and electrons, and improving the cycle performance and storage performance of the secondary battery.

[0110] In some embodiments, the gram capacity of the graphite negative electrode active material is greater than or equal to 340 mAh / g. In some embodiments, the gram capacity of the graphite negative electrode active material can be selected from any value of 340 mAh / g, 341 mAh / g, 342 mAh / g, 343 mAh / g, 344 mAh / g, 345 mAh / g, 346 mAh / g, 347 mAh / g, 349 mAh / g, 350 mAh / g, 351 mAh / g, 352 mAh / g, or a range consisting of any two of them.

[0111] The gram capacity can be measured by any known method in the art. For example, the graphite negative electrode active material sample can be mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a mass ratio of 91.6:1.8:6.6 in an appropriate amount of solvent NMP to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode and the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. CR2430 button cells are assembled in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the graphite negative electrode active material sample is the gram capacity of the graphite negative electrode active material.

[0112] Graphite negative electrode active materials have excellent gram capacity and can improve the energy density of secondary batteries.

[0113] In some embodiments, the gram capacity of the graphite negative electrode active material is 341 mAh / g-347 mAh / g. In some embodiments, the gram capacity of the graphite negative electrode active material can be selected as any value of 341 mAh / g, 342 mAh / g, 343 mAh / g, 344 mAh / g, 345 mAh / g, 346 mAh / g, 347 mAh / g, or a range consisting of any two of them.

[0114] The gram capacity of the graphite negative electrode active material is within the above range, the lattice expansion of the material during the cycle is relatively small, the crystal structure stability is good, the irreversible consumption of active ions is reduced, and the cycle performance and storage performance of the battery are improved.

[0115] The present application also provides a method for preparing a graphite negative electrode active material, which comprises the following steps:

[0116] Provide raw materials;

[0117] Processing the raw material to obtain a precursor;

[0118] The precursor is graphitized to obtain an intermediate product;

[0119] The intermediate product is subjected to screening treatment to obtain a graphite negative electrode active material; the graphitization degree of the graphite negative electrode active material is 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50ml / 100g.

[0120] By adopting the above preparation method, a graphite negative electrode active material with low oil absorption value and low graphitization degree can be prepared, which can further improve the cycle performance of the battery and extend the service life of the battery.

[0121] In some embodiments, the feedstock includes at least one of petroleum coke, needle coke, and pitch coke.

[0122] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0123] As used herein, the term "needle coke" refers to coal tar pitch or petroleum pitch, which, after undergoing liquid phase carbonization to generate an anisotropic mesophase, can generate coke with a needle-like texture after undergoing processes such as high-temperature carbonization.

[0124] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0125] In some embodiments, the feedstock comprises petroleum coke.

[0126] Petroleum coke has excellent anisotropy, which is conducive to the preparation of low-graphitization, low-expansion graphite negative electrode active materials, which is conducive to the long cycle life of the battery. At the same time, petroleum coke has high compaction density and high gram capacity, which is conducive to improving the energy density of the battery. In addition, the source of petroleum coke is more extensive, which is conducive to industrial production.

[0127] Based on the total volume of the raw material structure, the volume proportion of the mosaic type and regional type structure is greater than or equal to 50%.

[0128] According to the morphological characteristics and isochromatic zone size of the coke material under a polarizing microscope, its microstructure can be divided into mosaic type, regional type and fiber type. Usually, the isochromatic zone microstructure with a size less than 30μm is judged as mosaic type; the isochromatic zone microstructure with a size greater than 30μm is judged as regional type, and the anisotropic strip-shaped isochromatic zone is judged as fiber type structure.

[0129] In this application, the volume proportion of mosaic and regional structures in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with cement, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the mosaic-type and regional-type structure optical tissues by the total number of statistical testing points as the volume proportion of the mosaic-type and regional-type structures in the raw material.

[0130] In some embodiments, based on the total volume of the raw material structure, the volume proportion of the mosaic type and regional type structure is 50%-65%. In some embodiments, based on the total volume of the raw material structure, the volume proportion of the mosaic type and regional type structure can be any value of 50%, 55%, 60%, 65%, or a range consisting of any two values ​​thereof.

[0131] As mentioned above, a high volume proportion of mosaic and regional structures is conducive to obtaining graphite negative electrode active materials with low oil absorption values. However, if the volume proportion of mosaic and regional structures is too high, it will affect the gram capacity of the graphite negative electrode active materials and affect the energy density of the battery.

[0132] In some embodiments, the bonding index of the raw material is less than or equal to 10. In some embodiments, the bonding index of the raw material can be selected as any value of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or a range consisting of any two values ​​therein.

[0133] In some embodiments, the bonding index of the raw material is less than or equal to 1 to 9. In some embodiments, the bonding index of the raw material can be selected as any value of 1, 2, 3, 4, 5, 6, 7, 8, 9 or a range consisting of any two values ​​therein.

[0134] In this article, the term "bonding index" is used to characterize the bonding property of raw materials. It refers to the property that the raw materials form a plastic colloid during high temperature heating, which bonds itself or an external inert material and has a certain strength. It is a manifestation of the combined effect of the surface bonding and internal forces (adhesion and cohesion) of the colloid-like material.

[0135] In the present application, the adhesion index of the raw materials can be tested by methods known in the art. As an example, refer to GB / T5447-2014 / ISO 15585:2006 and use TX-600 to test the adhesion index. First, take 200g of sample and place it in a 100℃ drying oven for 1 hour; pass the dried sample through a sieve with a pore size of 200μm+100μm, and take samples under the 200μm sieve and on the 100μm sieve; then weigh 3.00±0.001g of special anthracite, and then weigh 3.00±0.001g of test sample and put it into the crucible, stir and mix evenly; use tweezers to clamp the pressing block and place it in the center of the crucible, then place it under the press, gently lower the pressure rod, and press for 30s; quickly put the crucible into the pre-heated muffle The crucible was taken out of the furnace and cooled, and the total weight of the sample was measured as m, and then the sample was placed in a rotary drum device for a rotary drum test; the sample after the rotary drum was sieved with a 1mm round hole sieve, and the weight of the sieve was weighed and recorded as m1; the sieve was placed in a rotary drum for a second rotary drum test, and then the sieve was sieved and weighed m2; the bonding index G was calculated according to the formula G = (30*m1+70*m2) / (5*m).

[0136] If the bonding index of the raw material is too high, the material is prone to bonding during the heat treatment process and to forming secondary particles, which makes the graphite negative electrode active material have a relatively irregular morphology. The graphite negative electrode active material has a large oil absorption value, which is not conducive to the dispersion of the negative electrode slurry and affects the cycle performance and storage performance of the battery.

[0137] In some embodiments, the processing of the raw material specifically comprises the following steps:

[0138] crushing, shaping and classifying the raw materials to obtain secondary raw materials;

[0139] Part of the fine powder in the secondary raw material is removed to obtain a precursor.

[0140] In some embodiments, in the step of crushing the raw material, a crusher, such as a jaw crusher, can be used to crush the raw material. For example, the raw material can be crushed to a set particle size before screening.

[0141] In some embodiments, in the step of shaping the raw material, a shaping machine can be used to shape the crushed raw material. The shaping process can reduce burrs on the surface of the crushed raw material, which is conducive to obtaining a rounded graphite negative electrode active material and a graphite negative electrode active material with a low oil absorption value.

[0142] In some embodiments, in the step of classifying the raw materials, an air flow classifier can be used to classify the shaped raw materials. Optionally, the induced air frequency can be greater than or equal to 20 Hz, and the classification frequency can be greater than or equal to 65 Hz. Classification can reduce the content of large particles and small particles in the precursor.

[0143] In some embodiments, the volume distribution particle size Dv50 of the precursor is 12 μm-18 μm. In some embodiments, the volume distribution particle size Dv50 of the precursor can be selected as any value of 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, or a range consisting of any two values ​​thereof.

[0144] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the precursor is 1.2-1.8. In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the precursor can be selected as any value among 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8 or a range consisting of any two values ​​therein.

[0145] Controlling the volume distribution particle size Dv50 or particle size distribution (Dv90-Dv10) / Dv50 of the precursor within a suitable range is conducive to controlling the particle size distribution (Dv90-Dv10) / Dv50 of the graphite negative electrode active material within a suitable range, thereby regulating the oil absorption value of the graphite negative electrode active material within a smaller range.

[0146] Herein, the term "graphitization treatment" refers to the heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.

[0147] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0148] In some embodiments, the maximum power of the graphitization treatment can be selected as 70%, 75%, 80%, 85%, 90% or any range of values ​​between the rated power of the graphitization treatment equipment. It can be understood that the graphitization treatment equipment refers to any device capable of graphitization treatment, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace and other devices. Among them, the rated power of graphitization treatment equipment produced by different manufacturers may be different, and it can be selected according to the actual situation.

[0149] The maximum power of graphitization used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process, ensure the consistency of the material's gram capacity, and help improve the cycle life of the battery.

[0150] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000W-32000W.

[0151] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000W-30000W.

[0152] In some embodiments, the maximum power of the graphitization process is 23000W-25000W.

[0153] For example, the maximum power of the graphitization process can be selected as 23000 W, 23500 W, 24000 W, 24500 W, 25000 W or any range therebetween.

[0154] By controlling the maximum power of the graphitization treatment, the graphitization degree of the graphite negative electrode active material during the heat treatment process can be effectively controlled, which is beneficial to improving the cycle life of the battery.

[0155] In some embodiments, the graphitization treatment is performed at a constant power time of 10 h to 50 h at the maximum power.

[0156] In some embodiments, the graphitization treatment is performed at a constant power time of maximum power of 10 h, 13 h, 16 h, 19 h, 22 h, 25 h, 28 h, 31 h, 33 h, 36 h, 39 h, 42 h, 45 h, 48 h, 50 h, or any range therebetween.

[0157] In some embodiments, the graphitization treatment equipment is an internal series furnace, and the graphitization treatment is performed at a constant power time of maximum power for 10 hours to 30 hours.

[0158] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment is performed at a constant power time of maximum power for 30 hours to 50 hours.

[0159] The appropriate maximum power constant power time is not likely to cause excessive rearrangement of the precursor, which can effectively reduce the specific surface area of ​​the graphite negative electrode active material, thereby improving the cycle performance of the battery; it can also effectively increase the gram capacity of the graphite negative electrode active material, which is beneficial to the energy density of the secondary battery.

[0160] In some embodiments, the screening process of the intermediate product specifically comprises the following steps:

[0161] The intermediate product is sieved to remove particles with a maximum particle size Dmax greater than 100 μm, thereby obtaining a graphite negative electrode active material.

[0162] Remove large-size particles from intermediate products to reduce the negative impact of large particle materials on battery cycle performance and storage performance.

[0163] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0164] [Negative electrode]

[0165] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes the graphite negative electrode active material of the first aspect of the embodiment of the present application or the graphite negative electrode active material prepared by the method described in the second aspect of the embodiment of the present application.

[0166] In some embodiments, the negative electrode film layer includes a conductive agent, and based on the mass of the negative electrode film layer, the mass content of the conductive agent is greater than or equal to 1.5%.

[0167] In some embodiments, based on the total mass of the negative electrode film layer, the mass proportion of the conductive agent is 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 3.0%, 3.1%, 3.2%, 3.2%, 3.3% or any numerical range therebetween.

[0168] During the battery cycle, active ions continue to embed and detach from the graphite negative electrode active material lattice, and the graphite negative electrode active material is prone to "isolation" of particles, thereby losing electrochemical activity, causing local current unevenness, polarization, accelerated capacity decay, and causing battery performance to "dive". In order to solve the above problems, a relatively high content of conductive agent is usually added to the negative electrode film layer to effectively enhance the electrical contact between the graphite negative electrode active materials and improve the cycle stability of the battery. However, adding a high content of conductive agent to the negative electrode slurry will affect the dispersibility of the negative electrode slurry. The graphite negative electrode active material with low oil absorption value of the present application has excellent dispersibility in the negative electrode slurry, which can make up for the effect of high content of conductive agent on the dispersibility of the negative electrode slurry.

[0169] The high content of conductive agent is matched with the graphite negative electrode active material with low oil absorption value. The negative electrode slurry has good dispersibility and the pole piece has excellent uniformity. At the same time, the graphite negative electrode active material has good electrical contact, which comprehensively improves the cycle performance of the battery.

[0170] In some embodiments, based on the mass of the negative electrode film layer, the mass content of the conductive agent is 1.8%-2.5%. In some embodiments, based on the total mass of the negative electrode film layer, the mass content of the conductive agent is 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5% or any range therebetween.

[0171] The mass proportion of the conductive agent is within an appropriate range, which can enhance the electrical contact between the graphite negative electrode active materials while not causing loss in the energy density of the battery due to excessive active conductive agent contained in the negative electrode film layer.

[0172] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0173] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0174] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite negative electrode active material. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0175] In some embodiments, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0176] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0177] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0178] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0179] [Positive electrode]

[0180] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.

[0181] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0182] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0183] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0184] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0185] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0186] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0187] [Electrolytes]

[0188] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0189] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0190] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0191] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0192] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0193] [Isolation film]

[0194] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0195] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0196] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0197] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0198] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0199] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0200] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0201] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0202] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0203] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0204] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0205] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0206] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0207] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0208] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0209] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0210] Example

[0211] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0212] Example 1

[0213] (1) Preparation of graphite negative electrode active materials

[0214] The petroleum coke having a volume ratio of 57.3% of the mosaic and regional structures and a bonding index of 6.2 is coarsely crushed, and then the coarsely crushed material is crushed and sieved, and the sieved material is shaped and graded. During the grading process, a certain amount of fine powder is removed to obtain a precursor, wherein the fine powder refers to particles with a volume distribution particle size Dv50 of 3-7 μm and a particle size distribution (Dv90-Dv10) / Dv50>1.6, and the volume distribution particle size Dv50 of the precursor is 16.2 μm, and the particle size distribution (Dv90-Dv10) / Dv50 of the precursor is 1.78;

[0215] The precursor is graphitized in an Acheson furnace at a graphitization temperature of 2800° C. The maximum power used in the graphitization is 23000W (herein, it refers to the actual power used by the Acheson furnace, which accounts for about 85% of the rated power of the Acheson furnace). After the power is kept constant for 40 hours, the surface temperature of the graphite crucible of the Acheson furnace is cooled to 200° C. to obtain an intermediate product;

[0216] The intermediate product was sieved and demagnetized to obtain a graphite negative electrode active material. The graphitization degree of the graphite negative electrode active material was 88%, the oil absorption value was 43ml / 100g, and the specific surface area was 0.92m 2 / g, Dv50 is 14.8μm.

[0217] (2) Preparation of negative electrode sheet

[0218] The graphite negative electrode active material prepared above, the conductive agent Super P, the thickener carboxymethyl cellulose CMC, and the binder styrene butadiene rubber SBR were mixed at a dry material mass ratio of 96:1:1.2:1.8, and deionized water was added as a solvent. The mixture was stirred under the action of a vacuum mixer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet was obtained after drying, cold pressing, and cutting. The compacted density of the negative electrode sheet is 1.50g / cm 3 , surface density is 9.6mg / cm 2 .

[0219] (3) Preparation of positive electrode sheet

[0220] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder polyvinylidene fluoride are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone is added. The system is stirred under the action of a vacuum mixer until it becomes uniform to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compacted density of the positive electrode sheet is 2.50g / cm 3 , surface density is 19.7mg / cm 2 .

[0221] (4) Preparation of electrolyte

[0222] In an argon atmosphere glove box with a water content of <10ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then sufficiently dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L, and vinylene carbonate is added to the above solution, the mass content of vinylene carbonate being 2% of the total mass of the electrolyte.

[0223] (5) Preparation of isolation membrane

[0224] Polypropylene film is used as the isolation film.

[0225] (6) Preparation of lithium-ion batteries

[0226] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0227] Example 2-3 is basically the same as Example 1, except that the bonding index of the raw material, the maximum power of the graphitization treatment and the particle size distribution of the precursor (Dv90-Dv10) / Dv50 are adjusted, as shown in Table 1.

[0228] Comparative Examples 1-3 are basically the same as Example 1, except that the volume proportion of the mosaic and regional structures in the raw materials, the bonding index of the raw materials, the maximum power of the graphitization treatment and the particle size distribution of the precursor (Dv90-Dv10) / Dv50 are adjusted, as shown in Table 1.

[0229] Table 1

[0230]

[0231]

[0232] Performance Testing

[0233] 1. Filtration time of negative electrode slurry

[0234] First, make sure the filter is 200 mesh, and cut it into 25cm*25cm with scissors. Find a clean 500ml beaker and make sure the beaker is clean. Fold the 150 mesh filter into a triangle, take 500ml of slurry and pour it from the top of the filter, pour it all at once, and start recording the time when the slurry starts to flow from the tip of the filter into the beaker. Record the time for 300ml filtration.

[0235] 2. Cycle performance test of secondary battery at 60℃

[0236] At 60°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0237] 3. Storage performance of secondary batteries at room temperature

[0238] In an environment of 25°C, the charge and discharge test was carried out, charging at a constant current of 1C to a voltage of 3.65V, then charging at a constant voltage of 3.65V to a current ≤0.05C, and then discharging the battery at a constant current of 1C to a voltage of 2.5V. This is a charge and discharge process, and the discharge capacity of the first cycle is recorded, which is the initial discharge capacity, recorded as C0. Then the fully charged battery cell is placed in an environment of 60°C for different periods of time, and the remaining capacity C1 is tested at 25°C every 30 days. This is a storage cycle, and the discharge capacity this time is the discharge capacity after the first storage. Subsequently, the first storage test process is repeated, the discharge capacity value during the storage process is recorded, and the 120-day cycle capacity retention rate is recorded.

[0239] 3. Results

[0240] As can be seen from Table 2, the graphite negative electrode active material provided in Examples 1-3 of the present application has a graphitization degree of 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50ml / 100g. As can be seen from the comparison between Examples 1-3 and Comparative Example 1, controlling the oil absorption value of the graphite negative electrode active material to be no more than 50ml / 100g can improve the dispersibility and filterability of the negative electrode slurry, and improve the cycle life and storage performance of the battery. As can be seen from the comparison between Examples 1-3 and Comparative Examples 2-3, controlling the graphitization degree of the graphite negative electrode active material to be 88%-93% can take into account both the gram capacity and the cycle performance of the graphite negative electrode active material, and the battery takes into account both high energy density and long cycle life, while also improving the storage performance of the battery.

[0241] From Examples 1-3, it can be seen that the specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g, the negative electrode slurry has excellent dispersibility and filterability, the graphite negative electrode active material has a high gram capacity, and the secondary battery has excellent cycle stability and storage stability.

[0242] It can be seen from Examples 1-3 that the volume distribution particle size Dv50 of the graphite negative electrode active material is 12-16 μm, the negative electrode slurry has excellent dispersibility and filterability, the graphite negative electrode active material has a high gram capacity, and the secondary battery has excellent cycle stability and storage stability.

[0243] Table 2

[0244]

[0245] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A graphite negative electrode active material, characterized in that: The graphitization degree of the graphite negative electrode active material is 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50ml / 100g.

2. The graphite negative electrode active material according to claim 1, characterized in that: The oil absorption value of the graphite negative electrode active material is 30 ml / 100 g to 43 ml / 100 g.

3. The graphite negative electrode active material according to claim 1 or 2, characterized in that: The particle size distribution of the graphite negative electrode active material (Dv90-Dv10) / Dv50 is 1.2-1.

6.

4. The graphite negative electrode active material according to any one of claims 1 to 3, characterized in that Based on the total number of particles of the graphite negative electrode active material, the number of primary particles in the graphite negative electrode active material accounts for greater than or equal to 85%, and can be optionally 85%-100%.

5. The graphite negative electrode active material according to any one of claims 1 to 4, characterized in that The specific surface area of ​​the graphite negative electrode active material is less than or equal to 1.4 m 2 / g, optional 0.6m 2 / g-1.3m 2 / g.

6. The graphite negative electrode active material according to any one of claims 1 to 5, characterized in that The volume distribution particle size Dv50 of the graphite negative electrode active material is 12-16 μm, and can be optionally 13-15 μm.

7. The graphite negative electrode active material according to any one of claims 1 to 6, characterized in that The graphite negative electrode active material satisfies at least one of the following: (1) The powder compaction density of the graphite negative electrode active material under a pressure of 49000N is less than or equal to 1.85g / cm 3 , optional 1.70g / cm 3 -1.85g / cm 3 ; (2) The tap density of the graphite negative electrode active material is 1.2 g / cm 3 -1.4g / cm 3 ; (3) The gram capacity of the graphite negative electrode active material is greater than or equal to 340 mAh / g, and can be optionally 341 mAh / g-347 mAh / g.

8. A method for preparing a graphite negative electrode active material, characterized in that: The steps include: Provide raw materials; Processing the raw material to obtain a precursor; The precursor is graphitized to obtain an intermediate product; The intermediate product is subjected to screening treatment to obtain a graphite negative electrode active material; the graphitization degree of the graphite negative electrode active material is 88%-93%, and the oil absorption value of the graphite negative electrode active material does not exceed 50ml / 100g.

9. The preparation method according to claim 8, characterized in that: The raw material includes at least one of petroleum coke, needle coke and pitch coke, and petroleum coke can be selected.

10. The preparation method according to claim 8 or 9, characterized in that: Based on the total volume of the raw material structure, the volume proportion of the mosaic type and regional type structure is greater than or equal to 50%, and can be optionally 50%-65%.

11. The preparation method according to any one of claims 8 to 10, characterized in that: The bonding index of the raw material is less than or equal to 10, and can be selected from 1 to 9.

12. The preparation method according to any one of claims 8 to 11, characterized in that: The precursor satisfies at least one of the following conditions: The volume distribution particle size Dv50 of the precursor is 12 μm-18 μm; and / or, The particle size distribution of the precursor (Dv90-Dv10) / Dv50 is 1.2-1.

8.

13. The preparation method according to any one of claims 8 to 12, characterized in that: The maximum power of the graphitization treatment is 70%-90% of the rated power of the graphitization equipment.

14. The preparation method according to claim 13, characterized in that: The maximum power of the graphitization treatment is 23000W-25000W; and / or the constant power time of the graphitization treatment at the maximum power is 10h-50h.

15. The preparation method according to any one of claims 8 to 14, characterized in that: The screening process of the intermediate product specifically comprises the following steps: The intermediate product is sieved to remove particles with a maximum particle size Dmax greater than 100 μm, thereby obtaining a graphite negative electrode active material.

16. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, characterized in that the negative electrode film layer includes the graphite negative electrode active material described in any one of claims 1 to 7 or the graphite negative electrode active material prepared by the preparation method described in any one of claims 8 to 15.

17. The secondary battery according to claim 16, characterized in that: The negative electrode film layer includes a conductive agent. Based on the mass of the negative electrode film layer, the mass content of the conductive agent is greater than or equal to 1.5%, and can be optionally 1.8%-2.5%.

18. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 16 or 17.

Citation Information

Patent Citations

  • Secondary battery, battery module including same, battery pack, and device

    CN114902450A

  • Negative active material, negative pole piece, lithium ion battery and electric equipment

    CN115000386A

  • Negative electrode material for lithium ion secondary battery, method for producing same, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    CN116686108A

  • Negative electrode material for lithium ion secondary battery, method for evaluating same, method for producing same, negative electrode for lithium ion secondary

    CN116783727A

  • Preparation method of isotropic coke as well as product obtained by preparation method and application of isotropic coke

    CN117143623A

Cited By

  • Battery cell, battery device, and electric device

    CN120357011A

  • Negative electrode active material made of graphite, secondary battery and power-consuming device

    DE202024002801U1

  • Graphite negative electrode active material and preparation method therefor, secondary battery, and electric device

    EP4811457A1